Eco-Green: Merubah Limbah Rumah Tangga Menjadi Bahan Baku Kompos - Arisudhana, Dicky; Lestari, Indah Rahayu; Laksmiwati, Mia; Arief, Rachmat; Brabo, Nora Andira; Iswati, Heni (Indonesian Journal of Emerging Trends in Community Empowerment, 2024)
Garbage is a problem faced in general, event at home. With so much waste that is not managed, it can harm the environment, even health. Waste from rubbish is one of the producer of both organic and inorganic waste. Based on the analysis of the situation that has been carried out, problems can be identified: (1) low knowledge of participants regarding environmental problems and effort to preserve the environments, (2) low motivational skills to preserve the environment, (3) lack of waste processing activities in the work environment and in the participant’s home environment. The method used in this activity is by conducting education, simulation and practice as well as evaluating the achievements of the activity which involves the entire team providing materials and training in making compost fertilizer. In this activity, composting activities began to be carried out. Participants are making process begins by adding dry media consisting of dry leaves obtained from around the garden. Dry leaves are chopped or shredded to facilitate the destruction process which is assister by natural microorganisms, then household waste which is wet waste is added. Composting from organic household waste went smoothly, and received an enthusiastic response from the participants. High awareness is needed from the public regarding contributes the largest amount of waste.